Jussaí (Euterpe edulis): a review - Lucia Maria Jaeger de CARVALHO (Food Science and Technology, 2022)
Abstract The fruit of the jussara palm (Euterpe edulis M.) from the Brazilian Atlantic Forest is rich in anthocyanins, mainly 3-O-glucoside cyanidin and 3-O-rutinoside cyanidin, with high antioxidant capacity which can prevent different types of diseases. The aim of this review addresses aspects of the fruit, proximate composition, bioactive compounds, main methods for determining the antioxidant activity as well as phenolic compounds, fruit processing and some products with functional properties.